Perceived Teacher Support and Communication in Strategizing Possible Selves - Mireles-Rios, Rebeca; Roshandel, Shadi (Frontiers in Education, 2020)
During high school, adolescents develop future plans for their lives and profession and teachers are generally believed to play an important role. At present, however, there is limited evidence about exactly how this support affects students. This study uses possible-selves theory to explore the link between perceived teacher support and communication about the future to adolescents’ own hoped-for and feared possible selves. Surveys and structured interviews were used to gather views of 85 Latina/o and White students (Mage = 15.5 years). Results indicate that greater perceived support and better communication from teachers were both associated with adolescents expressing more concrete strategies for achieving all types of possible selves. This study offers initial evidence about the important role teachers may play in supporting and shaping how adolescents construct an action plan that will lead to their desired future selves.